PENGARUH DIGITAL MARKETING INSTAGRAM PADA PUBLIC RELATIONS SCARLETT WHITENING DALAM MENINGKATKAN BRAND AWARENESS - Dewi, Qintania Diana; Widiasanty, Gita (Transpublika Publisher, 2023)
Scarlett Whitening is a skin & body care product from Indonesia that was founded in 2017. Public Relations Scarlett Whitening utilizes the development of Instagram digital marketing to increase brand awareness of its products. In this research we specifically discuss the influence of digital marketing on Instagram which consists of four indicators, namely content creation, content sharing, connection, community building and audience response to brand awareness which consists of not being brand aware, knowing the brand, brand recall, and brand recall at its peak. . This research aims to determine the influence of Instagram digital marketing on Scarlett Whitening's Public Relations in increasing brand awareness. This research method uses a quantitative approach with descriptive research type. Research data collection used a purposive sampling technique with the criteria of South Jakarta residents who follow Scarlett Whitening's Instagram social media. The research sample size used the Slovin formula and obtained 100 research respondents. Data collection was carried out by distributing online questionnaires using Google forms and processed using the SPSS (Statistical Program for Social Science) tool. The results of this research show that Instagram digital marketing at Public Relations Scarlett Whitening has had a significant influence in increasing brand awareness in the South Jakarta community.